Analisis Perencanaan Dan Pengendalian Persediaan Pasokan Bahan Baku Menggunakan Metode Economic Order Quantity - Mathilda Sri Lestari; Sri Hartanti; Dwi Awan Sulistiyanto (Program Studi Teknik Industri Universitas Setia Budi, 2022)
CV Bintang Timur Graphic is a company that produces learning tools for schools with a make-to-order production system. However, the ups and downs of production capability and capacity are one of the variables in inventory planning and control that needs to be controlled. Inventory control activities are very important for the company. If there is a stockout, the company cannot meet customer needs. Because consumer demand often fluctuates, especially in terms of quantity, type, or frequency. The inventory policy implemented at CV Bintang Timur Graphic does not use past historical data so excess or shortage of inventory often occurs. This study aims to analyze the number of raw material supplies, to be able to provide effective and efficient planning. The method used is the Economic Order Quantity (EOQ). The proposed inventory control plan using the EOQ method provides significant cost efficiency. Based on the results of the EOQ, 3 items have the highest efficiency ratings, including CD paper, which can save up to 81% of inventory costs, HVS Indigo Roll 73, which can save up to 72% of inventory costs, and 58.5x84 size paper, which can save up to 53% of inventory costs. For other raw material items, the average cost-saving efficiency reaches 35%. Then the application of the Economic Order Quantity (EOQ) method is appropriate for inventory control at CV Bintang Timur Graphic. Keywords: Efficiency, Fluctuation, Frequency, Make to Order, Production